Marketing Politik Pasangan Kepala Daerah dalam Pemilukada Kota Malang (Studi Kasus Tim Sukses Pemenangan Pasangan Abah Anton dan Sutiaji dalam Pemilukada Kota Malang 2013) - Saputra, Muchammad Ichsan (Jurnal Administrasi Publik, 2014)
Abstract: Political Marketing Mix Couple in the Regional Head Election (Case Study of Success Team Campaign Couple of Abah Anton and Sutiaji in Malang Election 2013). The use of science in marketing in the world of politics has been widely used in the election of the Head of the region. The importance of the role of marketing politics make candidates across Electoral Districts vying in the political marketing science as the key to success in businesses. No exception in the Head Region of Malang 2013, where couples Abaad Anton-Sutiaji (AJI) managed to win. This research result showed that political marketing that we have made in winning couples abah anton and sutiaji, namely the formation of a figure and programmes the campaign complex contain from politics, the determination of the product promotion, place, price and segmentation voters. In this case, the role of political marketing has been able to help couples abah anton and sutiaji winning general election in the city of Malang 2013. In this case, the role of political marketing has been able to help couples abah anton and sutiaji winning general election in the city of Malang 2013. Not separated from factors are both proponents and the economy in their trip. Supporting factors often regarded as things help in the campaign, the implementation of various programs while the economy is regarded as things factor that becomes an obstacle in running the strategy, whether it's a matter of technical and non technical. Keywords: election in Malang, Political marketing Â  Abstrak: Marketing Politik Pasangan Kepala Daerah dalam Pemilukada (Studi Kasus Tim Sukses Pemenangan Abah Anton dan Sutiaji dalam Pemilukada Kota Malang 2013). Penggunaan ilmu marketing dalam dunia politik telah banyak di gunakan pada Pemilihan Kepala Daerah. Peran dari marketing politik membuat para kandidat di seluruh pemilihan Kepala Daerah berlomba-lomba dalam mengkreasikan ilmu marketing politik sebagai kunci sukses dalam pemenanganya. Tidak terkecuali di pemilihan Kepala Daerah Kota Malang 2013 ini, dimana pasangan Abah Anton-Sutiaji (AJI) berhasil menang. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian ini menunjukan bahwa marketing politik yang telah dilakukannya dalam pemenangan pasangan Abah Anton dan Sutiaji, yaitu pembentukan figure dan program-program kampanye yang kompleks mecaukup dari penentuan produk politik, promotion, place, price dan segmentasi pemilih. Dalam hal ini, peran marketing politik telah membantu pasangan AJI dalam memenangkan Pemilukada Kota Malang 2013. Tidak terlepas dari adanya faktor pendukung dan penghambat di dalam perjalanannya. Kata Kunci: Pemilukada Kota Malang, marketing politikÂ